Analisis Strategi Pemasaran Online Dalam Upaya Meningkatkan Daya Saing Parfum Lokal Loco Pada Marketplace Shopee - Asya Sabrina Nur Amelia; Dea Amanda; Nabil Azizah Yulianti; Fathur Hisyam Zhafiri; Derizka Inva Jaswita (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The development of digital marketing has encouraged local business actors to utilize marketplaces as the main platform for promoting their products. The increasingly fierce competition in the perfume industry requires local brands to implement effective online marketing strategies to enhance their competitiveness. This study aims to analyze the online marketing strategies applied by the local perfume brand LOCO through the Shopee Live feature to increase its competitiveness in the Shopee marketplace. The research method used is qualitative descriptive, with the research object focusing on LOCO's marketing activities on Shopee. Data was obtained through observation, documentation, and analysis of Shopee Live performance data during the period from July to October 2025. The results of the study show that the use of Shopee Live contributed to an increase in product visibility, consumer interaction, and sales during specific periods. However, the study also indicates fluctuations in sales performance and consumer interaction, which were influenced by factors such as viewing duration, content quality, and operational challenges like stock limitations. Therefore, Shopee Live plays a role as an online marketing strategy that has the potential to enhance the competitiveness of LOCO’s local perfume brand if managed consistently and sustainably. Keywords: Online marketing strategy, Shopee Live, competitiveness, local perfume, e-commerce Abstrak Perkembangan pemasaran digital mendorong pelaku usaha lokal untuk memanfaatkan marketplace sebagai sarana utama dalam memasarkan produk. Persaingan yang semakin ketat di industri parfum menuntut brand lokal untuk menerapkan strategi pemasaran online yang efektif agar mampu meningkatkan daya saing. Penelitian ini bertujuan untuk menganalisis strategi pemasaran online yang diterapkan oleh parfum lokal LOCO melalui fitur Shopee Live dalam meningkatkan daya saing di marketplace Shopee. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan objek penelitian berupa aktivitas pemasaran LOCO di Shopee. Data diperoleh melalui observasi, dokumentasi, dan analisis data kinerja Shopee Live selama periode Juli–Oktober 2025. Hasil penelitian menunjukkan bahwa pemanfaatan Shopee Live berkontribusi terhadap peningkatan visibilitas produk, interaksi konsumen, serta penjualan pada periode tertentu. Namun, hasil penelitian juga menunjukkan adanya fluktuasi kinerja penjualan dan interaksi konsumen yang dipengaruhi oleh durasi menonton, kualitas konten, serta kendala operasional seperti keterbatasan stok. Dengan demikian, Shopee Live berperan sebagai strategi pemasaran online yang berpotensi meningkatkan daya saing parfum lokal LOCO apabila dikelola secara konsisten dan berkelanjutan. Kata kunci: Strategi pemasaran online, shopee live, daya saing, parfum lokal, e-commerce